ANALISIS STRATEGI PEMASARAN KERIPIK JAMUR TIRAM “KOOTI” PADA PT. ROEBY RUMAH PANGAN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Indah Miranti Rahayu; Nanik Dara Senjawati; Antik Suprihanti (Agrisociabus, 2022)
This study aimed to (1) identify internal and external factors that effect to the marketing of “Kooti” mushroom chips at the Roeby House, (2)analyze the marketing strategy of “Kooti” mushroom chips at Roeby House. The research method used descriptive method. The type of research was case study. Respondents were taken by using purposive sampling method. The data used are primary data and secondary data. The data sources methods used Focus Group Discussion (FGD), interviews, questionnaires, observations, and literature studies. Technical analysis used Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE). Internal External (IE) Matrix. Strength, Weakness, Opportunities, and Threats (SWOT) Matrix, and Quantitative Strategic Planning Matrix (QSPM). Result of the research showed that (1) Internal factors in the marketing business of "Kooti" mushroom chips at Roeby House were the product had save ingredients, attractive packaging, got an PIRT and had halal certificates, but human resources was not specialized yet according to the field of work, product brand was unpopular, and financial accounting had not good administrated. The external factor was had the opportunity for the promotion through internet, meanwhile the threats were more competitors with innovative products and the changes of consumer tastes. (2) Marketing strategies that can be used is maintaining and improving product quality.Keywords: Marketing Strategy, Mushroom Chips, SWOT